Analisis Pemanfaatan Teknologi Penghubung Lembaga Keuangan Syariah Dengan Usaha Mikro Kecil Menengah Untuk Meningkatkan Pangsa Pasar Syariah Di Yogyakarta - Deden Hardan Gutama; Avrillaila Akbar Harahap; Dhina Puspasari Wijaya (Jurnal Ilmiah SINUS, 2022)
User satisfaction is one of the important points for evaluating information systems or applications. Information systems or applications are said to be "good" if users are satisfied with the information system implemented in an organization and ADIBA MSME (Micro, Small, and Medium Enterprise) application is one of example. ADIBA MSME application is engaged in business economics. ADIBA MSME uses flutter platform with dart programming language. ADIBA MSME can map the distribution of closest LKS in Yogyakarta so that it can be accessed by Micro, Small, and Medium Enterprises (UMKM) actors. The existence of ADIBA MSME is expected to be the right solution in creating connectivity (link and match) between business actors and LKS so that the mobilization of LKS funds becomes more productive, effective, and efficient. Even though this app is already used, we still need to find whether users satisfy or not with this app. Therefore, we do this research to find that. The user satisfaction model in this study is End-User Computing Satisfaction (EUCS) and data processing methods to determine the relationship between indicators and construct to user satisfaction using SEM-PLS. The purpose of this study is to determine user satisfaction with ADIBA MSME application.